2021
DOI: 10.22270/jddt.v11i4.4890
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, ADMET and Druggable properties of Myricetin: A Key Flavonoid in Syzygium cumini that regulates metabolic inflammations

Abstract: Syzygium cumini (Myrtaceae) is a potential medicinal plant traditionally used in indigenous systems of medicines practiced in India and elsewhere due to its functional properties against metabolic inflammations viz., anti-hyperglycemic, anti-inflammatory, cardio-protective, and antioxidant activities. Targeting metabolic inflammation has emerged as a standalone strategy to attenuate metabolic disease. Myricetin (3,5,7,3′,4′,5′-hexahydroxyflavone) is one of the flavonoids from stem bark, leaf, flowers, fruits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…The qualitative assessment of pharmacokinetics viz; absorption, distribution, metabolism, excretion and toxicity (ADMET) profile of selected compounds were predicted computationally by using SwissADME and toxicity prediction using TOPKAT (Accelrys, Inc., USA). QikProp develops and employs QSAR/QSPR models using partial least squares, principal component analysis and multiple linear regression to predict physicochemical significant descriptors [68][69][70]…”
Section: Admet Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative assessment of pharmacokinetics viz; absorption, distribution, metabolism, excretion and toxicity (ADMET) profile of selected compounds were predicted computationally by using SwissADME and toxicity prediction using TOPKAT (Accelrys, Inc., USA). QikProp develops and employs QSAR/QSPR models using partial least squares, principal component analysis and multiple linear regression to predict physicochemical significant descriptors [68][69][70]…”
Section: Admet Predictionmentioning
confidence: 99%
“…Recently, it has been reported that abundance of Que in different plant parts of Artemisia annua may be exploited for the treatment of coronavirus 61 . With this background information pharmacological characterization is expected to further validate Que as novel drug lead [62][63][64][65][66][67][68] .…”
Section: Introductionmentioning
confidence: 99%
“…Selected phytocompounds were subjected to ADMET prediction (SwissADME) and toxicity prediction using TOPKAT (Accelrys, Inc., USA). QikProp develops and employs QSAR/QSPR models using partial least squares, principal component analysis and multiple linear regression to predict physic-chemically significant descriptors [33][34][35] .…”
Section: Admet Predictionmentioning
confidence: 99%
“…Azadirachtin has been identified as potential inhibitor of SARS-CoV-2 main protease [62][63][64] and is expected to play a major role in the management of COVID-19. Furthermore, pharmacological characterization is expected to validate Azadirachtin as novel drug lead [65][66][67][68] . 33 .…”
Section: Introductionmentioning
confidence: 99%